PERANAN PEMERINTAH DALAM MENGAWASI TAKARAN DAN TIMBANGAN: Perspektif Ekonomi Islam - Rozalinda Rozalinda (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The history of Islamic economics uncovers that weight and measurement tools used by traders or sellers wereregularly supervised by the government’s institution, called al-ḥisba. Parallel to this historical fact, in Indonesiathe similar institution is currently placed under the authority of the Ministry of Trade and Commerce regulatedunder the Law No.2 of 1981. This study focuses to the actual practices of the law. Data for this study is gatheredfrom conducting serial interviews with traders, the authorities and conducting observation to the marketsactivities. The finding reveals that the authorized institution has not yet worked effectively in conducting itstasks that limitedly applies a seal to the measurement tools. These practices have untouched moral aspect of thebusiness activities. It hardly stepped forward to supervise the traders and sellers and also hardly applied lawenforcement. It suggests that this authorized institution, such as al-ḥisba, has the authority to enforce the lawin the framework of amar ma’ruf nahy munkar.